Progress and experiences of implementing an integrated disease surveillance and response system in Somalia; 2016–2023 - Ssendagire, Steven; Karanja, Mary Joan; Abdi, Abdulkhadir; Lubogo, Mutaawe; Azad Al, Abdullah; Mzava, Khadija; Osman, Abdinasir Yusuf; Abdikarim, Ahmed Mohamed; Abdi, Mohamed Abdirahman; Abdullahi, Abdirahman Mohamed; Mohamed, Abdirizak; Ahmed, Hussein Sheik; et al. (Frontiers in Public Health, 2023)
Introduction In 2021, a regional strategy for integrated disease surveillance was adopted by member states of the World Health Organization Eastern Mediterranean Region. But before then, member states including Somalia had made progress in integration of their disease surveillance systems. We report on the progress and experiences of implementing an integrated disease surveillance and response system in Somalia between 2016 and 2023. Methods We reviewed 20 operational documents and identified key integrated disease surveillance and response system (IDSRS) actions/processes implemented between 2016 and 2023. We verified these through an anonymized online survey. The survey respondents also assessed Somalia’s IDSRS implementation progress using a standard IDS monitoring framework Finally, we interviewed 8 key informants to explore factors to which the current IDSRS implementation progress is attributed. Results Between 2016 and 2023, 7 key IDSRS actions/processes were implemented including: establishment of high-level commitment; development of a 3-year operational plan; development of a coordination mechanism; configuring the District Health Information Software to support implementation among others. IDSRS implementation progress ranged from 15% for financing to 78% for tools. Reasons for the progress were summarized under 6 thematic areas; understanding frustrations with the current surveillance system; the opportunity occasioned by COVID-19; mainstreaming IDSRS in strategic documents; establishment of an oversight mechanism; staggering implementation of key activities over a reasonable length of time and being flexible about pre-determined timelines. Discussion From 2016 to 2023, Somalia registered significant progress towards implementation of IDSRS. The 15 years of EWARN implementation in Somalia (since 2008) provided a strong foundation for IDSRS implementation. If implemented comprehensively, IDSRS will accelerate country progress toward establishment of IHR core capacities. Sustainable funding is the major challenge towards IDSRS implementation in Somalia. Government and its partners need to exploit feasible options for sustainable investment in integrated disease surveillance and response.